PEMBUATAN APLIKASI PENYIMPANAN OBAT (APO) DALAM PENGONTROLAN MASA KADALUARSA OBAT DI APOTEK BERBASIS WEB - Fitrah Shafran Ilahi; Abdul Mahmud Yumassik; Mochammad Maulidie Alfiannor Saputera (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
Digital pharmacy has been growing in the current era, so the need for an application to help the performance of a pharmacist is indispensable. Pharmacy management information system applications that have been circulating are known to have not used a drug expiration date notification system to email. The purpose of this study was to find out whether the drug storage application design can control drug expiration in a website-based pharmacy. The research method is carried out by making website-based software by applying data flow diagrams (DFD). The research procedure is to first design a data flow diagram consisting of drug data input, purchase transaction data input, sales transaction data input, drug storage data input and transaction report input. After that, create a use case design consisting of two, namely admin and cashier. The last step is to create a block diagram flow with notifications of drugs approaching expiration in the form of incoming e-mails to users. The results showed that the design of the drug storage application system that was made could operate properly and had been tested independently. The drug storage application has not yet been tested by the public, so further testing is needed.